Edukasi Gizi dan Stimulasi Tumbuh Kembang sebagai Upaya Meningkatkan Kualitas Hidup Anak dan Remaja di Desa Sajen, Mojokerto - Maria Natalia Indawati; Florence Pribadi; Areta Idarto; Gladys Adipranoto; Denys Putra Alim (Jurnal Informasi Pengabdian Masyarakat, 2026)
Nutritional status and growth and development stimulation are important factors influencing the quality of life of children and adolescents. Low parental health literacy regarding nutrition and developmental stimulation may increase the risk of growth disorders, developmental delays, and decreased children’s health-related quality of life (HRQoL). This community service program aimed to improve community knowledge regarding balanced nutrition and child growth and development stimulation through community-based education in Sajen Village, Pacet District, Mojokerto Regency. The program was conducted through interactive health education sessions, discussions, demonstrations of developmental stimulation, and the distribution of educational media in the form of leaflets and booklets. Evaluation was performed using pre-test and post-test methods to assess changes in participants’ knowledge after the intervention. The evaluation results demonstrated an improvement in participants’ understanding of balanced nutrition, growth and development stimulation, and the role of parents in supporting children’s quality of life. The participatory educational approach increased participant engagement and facilitated more effective health information transfer. This activity indicates that community-based nutrition and developmental stimulation education can serve as an effective promotive and preventive strategy to improve public health literacy and support the optimization of children’s growth, development, and quality of life in rural communities.